Well-differentiated Adenocarcinoma Arising from Gastric Cystica Profunda Treated by Endoscopic Submucosal Dissection: A case report and literature review - Huang, Cao; Liu, Jiang (Zeitschrift für Gastroenterologie, 2025)
Gastritis cystica profunda (GCP) is a rare disease that is often observed at the stoma site of patients undergoing gastric surgery. Specific symptoms are often lacking, making it difficult to diagnose. GCP may develop into cancer. Endoscopic resection is a good method to reduce surgical injury, and the therapeutic effect depends on the status of the primary disease.The patient was a 77-year-old male who was admitted to the hospital for repeated epigastric distention. The man had never undergone gastric surgery and did not have Helicobacter pylori infection. Physical and laboratory tests showed no abnormality. Computed tomography showed no significant abnormality. Endoscopy revealed multiple ulcers on the posterior wall of the gastric body, but biopsy showed no evidence of malignancy. The patient subsequently underwent ESD surgery with a lesion of 1.5 cm×2.3 cm. Pathological results showed the cystic dilatation of gastric glands in the submucosa, with some well-differentiated adenocarcinoma. The final diagnosis was GCP with well-differentiated gastric adenocarcinoma.Herein, we describe a case of ESD therapy for GCP with well-differentiated gastric adenocarcinoma. When gastric mucosal lesions are difficult to diagnose, further treatment and diagnosis with EMR or ESD can be considered. For patients with early gastric cancer, long-term postoperative monitoring should be carried out.
Keywords: Endoscopic submucosal dissection; Gastric cancer; Well-differentiated adenocarcinoma; Gastritis cystica profunda